How deep learning identifies and learns aspects of plant for classification - Devi V. Sowmya; Pooja Govu; Ramya Sande; Priya Nakka Vishnu (ITM Web of Conferences)
Identification of plant species is very crucial for preserving biodiversity, developing farm-based practices and ecosystem administration. By merging classical structural approach with innovative machine learning methods. We gathered data from diverse plants highlighting mainly on leaves, fruits, flowers and vegetables. Focusing on their dimension, outline and their features, and also environmental factors like climate and soil type. To extract optimal features which are missed by the traditional methods to overcome this we took high quality snapshots with advanced image processing methods. Convolutional Neural Network (CNN) of supervised learning algorithm used along with the Keras and Tensorflow the features were analysed and deployed in Streamlit. Accomplishing an accuracy of 95% on a dataset which was trained over 10,000 plant samples with conventional strategies. The outcomes boost the process and also improves identification by making reliable tool and helps for ecologists, botanists and agricultural scientists. This study achieves a robust solution for plant species identification by integrating advanced algorithms and traditional techniques. It encourages for conservation analysis and wildlife protection initiatives.